Spatial organization in bacterial chemotaxis - Sourjik, Victor; Armitage, Judith P. (The EMBO journal, 2010)
Victor Sourjik and Judith Armitage outline the organization and differing complexity of chemotaxis pathways in Escherichia coli and Rhodobacter sphaeroides.
Gesehen am 28.09.2023